Pedagogical technology of developing students’ readiness for independent educational activities in the environment of digital training of professional education (Global Scientific Review, 2024)
This article methods and means of activity of the audience in the digital educational environment , the student’s independent learning, learning and mastering under the guidance of the teacher in the process of pedagogical technology are presented